2013
DOI: 10.1021/jp310961a
|View full text |Cite
|
Sign up to set email alerts
|

Poling Induced Mass Transport in Thin Polymer Films

Abstract: In this study we report investigation of the polymer film morphology modifications during their corona poling for fabrication of nonlinear optically (NLO) active materials. We demonstrate that at certain poling conditions surface and spatial inhomogeneities in the poled area of the sample appear. Densities of the inhomogeinities depend on the strength of the poling field, the sample temperature during the poling, and the prepoling conditions. Optimization of the poling conditions directed toward avoiding surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Secondly, the sputtering of electrodes for the EO coefficient measurements may cause a local heating and depolarization of the polymer. Thirdly, we suggest that the inaccuracy of the EO coefficient measurement could also arise from overestimation of the actual modulating electric field on the sample on account of two effects: (i) the poled polymer could have some pinholes which appear after the corona poling process and may cause the effective voltage drop on the thin film to be reduced ; (ii) due to the contact resistance and the capacitive nature of the sample it could operate as a filter lowering the amplitude of the modulating electric field. This could also explain why the determined EO coefficients using TM and MZI methods are by an order lower than the ones determined by the ATR method in which the modulating electric field is applied only at the light coupling point.…”
Section: Comparison Of Measured Eo and Nlo Coefficientsmentioning
confidence: 99%
“…Secondly, the sputtering of electrodes for the EO coefficient measurements may cause a local heating and depolarization of the polymer. Thirdly, we suggest that the inaccuracy of the EO coefficient measurement could also arise from overestimation of the actual modulating electric field on the sample on account of two effects: (i) the poled polymer could have some pinholes which appear after the corona poling process and may cause the effective voltage drop on the thin film to be reduced ; (ii) due to the contact resistance and the capacitive nature of the sample it could operate as a filter lowering the amplitude of the modulating electric field. This could also explain why the determined EO coefficients using TM and MZI methods are by an order lower than the ones determined by the ATR method in which the modulating electric field is applied only at the light coupling point.…”
Section: Comparison Of Measured Eo and Nlo Coefficientsmentioning
confidence: 99%
“…Crystallization of EO chromophores can cause lower EO efficiency, higher probability of dielectric breakdown and larger propagation loss. Secondly, the Maker fringe measurements performed at 1064 nm with a setup described elsewhere [33] done after corona poling [34] showed that DMABI-Ph6 possesses a high NLO coefficient -d33(532) = 69.2 pm/V. For this material the NLO coefficient values are resonantly enhanced due to the fact that the second harmonic of 1064 nm is in the absorption band.…”
Section: Eo Polymermentioning
confidence: 97%